Marine biodegradation of poly[(R)-3-hydroxybutyrate-co-4-hydroxybutyrate] elastic fibers in seawater: dependence of decomposition rate on highly ordered structure - Omura, Taku; Tsujimoto, Sakura; Kimura, Satoshi; Maehara, Akira; Kabe, Taizo; Iwata, Tadahisa (Frontiers in Bioengineering and Biotechnology, 2023)
Here, we report the marine degradability of polymers with highly ordered structures in natural environmental water using microbial degradation and biochemical oxygen demand (BOD) tests. Three types of elastic fibers (non-porous as-spun, non-porous drawn, and porous drawn) with different highly ordered structures were prepared using poly[(R)-3-hydroxybutyrate-co-16 mol%-4-hydroxybutyrate] (P(3HB-co-16 mol%-4HB)), a well-known polyhydroxyalkanoate. Scanning electron microscopy (SEM) images indicated that microorganisms attached to the fiber surface within several days of testing and degraded the fiber without causing physical disintegration. The results of BOD tests revealed that more than 80% of P(3HB-co-16 mol%-4HB) was degraded by microorganisms in the ocean. The plastisphere was composed of a wide variety of microorganisms, and the microorganisms accumulated on the fiber surfaces differed from those in the biofilms. The microbial degradation rate increased as the degree of molecular orientation and porosity of the fiber increased: as-spun fiber < non-porous drawn fiber < porous drawn fiber. The drawing process induced significant changes in the highly ordered structure of the fiber, such as molecular orientation and porosity, without affecting the crystallinity. The results of SEM observations and X-ray measurements indicated that drawing the fibers oriented the amorphous chains, which promoted enzymatic degradation by microorganisms.